The microbial pharmacists within us: a metagenomic view of xenobiotic metabolism - Spanogiannopoulos, Peter; Bess, Elizabeth N.; Carmody, Rachel N.; Turnbaugh, Peter J. (Nature reviews. Microbiology, 2016)
Key Points The gut microbiome is a neglected component of the first-pass metabolism of xenobiotics before reaching the general circulation. Direct microbial metabolism of xenobiotics and their metabolites often involves reduction or hydrolysis, but most of the enzymes responsible for these reactions remain unknown. Microbial metabolism influences both efficacy and toxicity, producing bioactive compounds, inactive metabolites and toxins. Relevant host–microbial interactions include the expression of host genes that are involved in drug transport and metabolism, the interference with host enzymatic activity and the modulation of immune responses. The translational implications of these studies include the development of novel co-therapies and the identification of new biomarkers and drugs. In this Review, Turnbaugh and colleagues discuss several mechanisms by which the human gut microbiome affects the metabolism of xenobiotics, including drugs and dietary compounds, and explore how this knowledge can be applied to improve the treatment of human disease. Although the importance of human genetic polymorphisms in therapeutic outcomes is well established, the role of our 'second genome' (the microbiome) has been largely overlooked. In this Review, we highlight recent studies that have shed light on the mechanisms that link the human gut microbiome to the efficacy and toxicity of xenobiotics, including drugs, dietary compounds and environmental toxins. Continued progress in this area could enable more precise tools for predicting patient responses and for the development of a new generation of therapeutics based on, or targeted at, the gut microbiome. Indeed, the admirable goal of precision medicine may require us to first understand the microbial pharmacists within.